2007
DOI: 10.1007/s11255-007-9219-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential predictive factors of positive prostate biopsy in the Japanese population

Abstract: This study investigated potential predictors for positive prostate biopsy and demonstrated that prostate volume was an independent predictive factor for positive prostate biopsy in patients with PSA levels <10 ng/ml. In the future, we may be able to use our findings to create a nomogram for predicting positive prostate biopsy in Japanese men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(22 reference statements)
1
1
0
Order By: Relevance
“…We analyzed prostate volume to find the direct effect of prostate volume on prediction of histopathology of biopsy rather than the calculation PSA density. According to the study of Shigemura et al in Japanese men with PSA levels <10 ng/ml showed that prostate volume was the significant predictor for a positive biopsy (Shigemura et al, 2008).Based on our findings, prostate volume >40 cc should be considered a predictive factor for a positive biopsy (p=0.0001). On the other hand prostate volume was not included in Garzotto's study which reports independent factors associated with positive biopsy (Garzotto et al, 2003).…”
Section: 6085 Impact Of Psa and Dre On Histologic Findings At Prostasupporting
confidence: 57%
“…We analyzed prostate volume to find the direct effect of prostate volume on prediction of histopathology of biopsy rather than the calculation PSA density. According to the study of Shigemura et al in Japanese men with PSA levels <10 ng/ml showed that prostate volume was the significant predictor for a positive biopsy (Shigemura et al, 2008).Based on our findings, prostate volume >40 cc should be considered a predictive factor for a positive biopsy (p=0.0001). On the other hand prostate volume was not included in Garzotto's study which reports independent factors associated with positive biopsy (Garzotto et al, 2003).…”
Section: 6085 Impact Of Psa and Dre On Histologic Findings At Prostasupporting
confidence: 57%
“…63,[83][84][85] In order to predict a positive biopsy, some parameters and nomograms can be used, such as positive digital rectal examination results, prostate volume and hypo-echoic lesions on TRUS. 65,[86][87][88][89][90][91][92][93] For patients with clinically suspected PCa but a negative first biopsy, a saturation biopsy (minimum of 20 cores) with lateral and apical cores may be indicated, which is also efficacious for staging patients who are undergoing active surveillance protocols, 63,85,94,95 Pepe et al 96 suggested that in addition to the presence of LUTS, TURP should be a part of the diagnostic procedure in cases of a repeated negative saturation biopsy. Meanwhile, the sample from the prostatic transition zone by directed needle biopsies may be omitted due to a lower detection rate compared to TURP.…”
Section: Prostate Cancer (Pca) Epidemiological Characteristicsmentioning
confidence: 99%